IMPLEMENTASI STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN PADA UMKM RUMAH DODOL LEMBANG - Siti Silviah; Alda Ramadhika (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
The marketing aspect is one of the problems experienced by UMKM in Indonesia.Therefore, this research aims to find out how marketing strategies are implemented in increasing sales of Rumah Dodol Lembang and also the external and internal factors of Rumah Dodol Lembang. This research is descriptive qualitative research using primary and secondary data. Techniques for collecting data using interviews and documentation. The results of this research show that Rumah Dodol Lembang is a quality product that is different from other products, the price is set in accordance with the quality of the product, the distribution place is easy to reach, and the promotions are carried out online and in person. In terms of advantages (internal), it has quality products, products that are different from others, and already has Halal certification. In terms of product weakness, Rumah Dodol Lembang is that production is still relatively small. In terms of opportunities (external), Rumah Dodol Lembang products have competition that does not yet exist with similar products. The threats are the increase in raw material prices and the scarcity of bamboo packaging. Implementing a good marketing strategies Rumah Dodol Lembang can increase sales by up 20% / year.